Pendampingan Pembelajaran Koding dan Kecerdasan Artifisial Pada Guru di TK Bina Generasi, Tobelo, Halmahera Utara - Haryati; Puji Dwi Rahayu rahayu; Nuraini Mokan (BALE LITERASI, 2026)
This community service program was carried out to enhance the competence of teachers at TK Bina Generasi, Tobelo, North Halmahera, in understanding and implementing coding instruction and artificial intelligence (AI) in early childhood education. The program was motivated by low digital literacy and the limited comprehension of teachers regarding basic coding concepts—particularly unplugged coding methods—as well as the minimal integration of AI-based technology in learning activities. The community service activities were conducted over two days through several stages: needs assessment, material development, technical training, classroom practice assistance, and learning process evaluation. The training covered the introduction of early childhood coding concepts, the application of unplugged coding through play-based media, and fundamental AI concepts relevant to early childhood education. The results show an improvement in teachers’ understanding of coding and AI, as well as their ability to design learning activities based on logic, patterns, and systematic steps. Teachers were also able to implement unplugged coding activities for young children in creative and contextual ways. Supporting factors included high teacher enthusiasm, strong support from the school principal, and the availability of practical training materials. The main obstacles encountered were limited technological devices and varying levels of digital literacy among teachers. Overall, this community service program had a positive impact on enhancing digital competence among early childhood educators and opened opportunities for further development of technology-based learning at TK Bina Generasi in the future.